Do investors of Islamic equity funds follow Warren Buffet’s advice? a regression assessment - Maimunah Johari,; Nor Balkish Zakaria,; Aziatul Waznah Ghazali,; Raja Adzrin Raja Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Researchers have doubted Islamic funds’ ability to provide promising financial returns due to the shariah screening procedures. Despite its popularity, Islamic funds are still in doubt to generate attractive returns. Survival of Islamic funds is highly contingent on their capacity to foresee Shariah compliance opportunities in economic shifts. Investors defer fund withdrawal of the worst-performing funds and anticipate the manager will adjust the fund’s investing strategy for a future with higher yields. Thus, this paper aims to investigate investors’ reactions to the Islamic equity fund results (IEs) according to the opportunity motive of Warren Buffet. This is accomplished by evaluating the relationship between fund flow and performance. This allows us to determine whether investors behave toward the greatest and worst performing funds by transferring cash into or out of the funds. This study uses panel data analysis to investigate 134 IEs from 2007 through 2019. The findings revealed that the link between fund flow and performance of IEs is incompatible with the asymmetric relationship, implying that the cash outflow for poorly performing funds declined. In contrast, cash inflow fell for funds that performed the best. Consistent with Warren Buffet’s advice.